IMPLEMENTASI KEBIJAKAN KETERBUKAAN INFORMASI PUBLIK PADA BADAN PUBLIK SEKTOR SUMBER DAYA ALAM DI PROVINSI KALIMANTAN TIMUR - Muhammad Rizqi Rahmani (Magister Administrasi Publik FISIP Universitas Mulawarman, 2021)
This article will discuss the comparison and analysis of public information disclosure laws at the Plantation, Environment, Forestry, Energy and Mineral Resources Office in East Kalimantan Province. The methodology used is in the type of comparative research, where data is collected and analyzed that is narrative in nature, as well as in-depth information about the issues or problems to be solved. The research findings indicate that the public information disclosure policy has been implemented, but not optimal.Keywords: Implementation, Openness, Information, Public